Will Christianity Survive in the Middle East? - V. Popov (Международная аналитика, 2015)
The paper briefly outlines the history of relationships between Christianity and Islam in the Middle East, the birthplace of both great religions. For many centuries these relationships were characterized by the atmosphere of tolerance, moderation, and dialogue. Christians in Islamic world, in spite of sporadically emerging tensions and conflicts, historically were always a significant and respectable social and cultural group.The conditions of Christians, and especially Orthodox Christians, seriously aggravated in the second half of the 19th century. Armenians, Greeks, Assyrians who were the victims of Young Turkish genocide of the First World War were mostly Christians. The 20th century saw the exodus of Christians from the Middle East the dynamics of which in the last decades is becoming more and more impressive.The paper adduces numerous examples of worsening positions of Christian Communities in the Middle East, together with an analysis of reasons behind this state of affairs. The question of chances to slow down the negative developments is also considered at some length.